Explaining the political nature of environmental impact assessment (EIA): A neo-Gramscian perspective. (20th January 2020) - Bond, Alan; Pope, Jenny; Fundingsland, Monica; Morrison-Saunders, Angus; Retief, Francois; Hauptfleisch, Morgan
Abstract: Environmental Impact Assessment (EIA) is a mandatory decision-support tool in every country of the world, developed 50 years ago to ensure the consideration of the environmental consequences of development decisions prior to approval decisions being made. Specifically, the aim of developing an EIA system was to make decision-making affecting the environment more accountable, through the use of objective scientific evidence. It remains the project decision-support tool of choice despite considerable research efforts failing to provide convincing evidence that it achieves this aim. Here we explain this apparent paradox by arguing that EIA supports neoliberal agendas by facilitating economic development. We present arguments based on a neo-Gramscian perspective that explains how apparent advances in the practice of EIA are sanctioned because they actually maintain the political nature of the EIA system, which continues to undermine attempts to use evidence objectively. We use a narratives of change approach to support this perspective. We conclude that EIA can only make decision-making more accountable if strategies to depoliticise it are employed, including emphasising substantive outcomes.